Teaching Narrative Reading By Applying Think-Pair-Share Model - Meli Damayanti (Darussalam English Journal, 2022)
The main problem of this study was: Is it effective to Apply the Think-Pair-Share Model in teaching narrative reading comprehension to the eleventh-grade students of the Sriwijaya State Sports High School of Palembang? The method used in this research was the quasi-experimental method. The population of this study was all of the Eleventh Grade Students of SMA Olahraga Negeri Srwijaya Palembang in the academic year of 2021/2020. The sample of this study was classes XI. IPA 1 and XI. IPA 3 was taken through convenience nonrandom sampling. The data was collected through a reading comprehension test. They were pre-test and post-test. The data were analyzed through a t-test formula. From this study it was found that the students’ pre-test average score in the experimental group was 55 and in the control group was 53.91. Meanwhile, the students’ post-test average score in the experimental group was 80 and the student's average score in the control group was 75. In addition of t-obtained were 2.049 where the value of t-table was 1.684 at df 74 in significance level of 0.05 and with one-tailed testing. Since the value of the t-obtained was higher than the critical value of the t-table (2.049>1.684), it can be concluded that teaching reading comprehension by Applying the Think-Pair-Share Model to the Eleventh Grade Students of SMA Olahraga Negeri Sriwijaya Palembang was effective